Persistência no solo, seletividade para espécies cultivadas e interação de saflufenacil com herbicidas causadores de estresse oxidativo - Diesel, Francielli (2013)
Saflufenacil is a new herbicide which is being deployed commercially in Brazil. Many factors are necessary toward successful of commercially herbicide, among them stands out the selectivity for interests crops, the effectiveness under weed species and the environment safety. In the first one were experienced seven periods of sowing bean after saflufenacil application (0, 5, 10, 15, 25, 35 e 50 AHA) in the absence and presence of saflufenacil herbicide (0 e 29,4 g a.i. ha-1). In the second one two saflufenacil concentrations (0; 14,7 e 29,4 g a.i. ha-1) were tested into ten bean cultivars. For both tests were determined the stand, plant high, yield and yield components. The first bioassay was carried out in a completely randomized design (CRD) with three replications in a factorial design 8 x 5 x 4, where the first factor is saflufenacil concentrations (0, 2.45, 4.9, 9.8, 14.7, 19.6, 24, 5 and 29.4 g ai ha-1), the second the bioindicators cucumber, watermelon, cabotiá, summer squash and beets the third factor periods (5, 10, 15 and 20 DAS). Evaluations were performed booth and plant height, mass of fresh (MPAV) and dry (MPAS) shoots. The second and third bioassays were conducted simultaneously, and the treatments consisted of soil sampling times after saflufenacil spraying (29.4 g ai ha-1) (0, 5, 10, 15, 25, 35 , 50 and 100 days). In one bioassay we used cucumber and in the second we used beet as biomarkers for the presence of saflufenacil the soil. The same variables were determined from the first bioassay. Treatments were saflufenacil (0, 0.35, 0.7, 1.4, 2.1 and 2.8 g ai ha-1) applied alone or combined with paraquat (0, 1 and 3 g ai ha-1 ), metribuzin (0, 38.4 and 105.6 g ai ha-1) and clomazone (0, 288 and 504 g ai ha-1). The evaluated variables were visual control, and MPAV MPAS. The application of pre-emergence saflufenacil requires between 10 and 25 days after application to be performed seeding bean cultivar IPR-Tiziu. The BRS Talismã cultivar showed higher tolerance to saflufenacil, while the cultivar Jalo Precoce showed greater sensitivity to the herbicide. The species with the highest sensitivity to saflufenacil were cucumber and beet. The persistence of saflufenacil in Latossolo Vermelho distroférrico determined by bioassay with cucumber and beets, was between 25 and 35 days after herbicide application. For the A. tenella control, there was synergism for combinations saflufenacil with higher doses of paraquat and metribuzin, but not with clomazone. For MPAV and MPAS, all associations were synergistic, independently of herbicide or dose that was used.